2014
DOI: 10.1155/2014/902038
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruziInfection and Host Lipid Metabolism

Abstract: Trypanosoma cruzi is the causative agent of Chagas disease. Approximately 8 million people are thought to be affected worldwide. Several players in host lipid metabolism have been implicated in T. cruzi-host interactions in recent research, including macrophages, adipocytes, low density lipoprotein (LDL), low density lipoprotein receptor (LDLR), and high density lipoprotein (HDL). All of these factors are required to maintain host lipid homeostasis and are intricately connected via several metabolic pathways. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 108 publications
2
20
0
Order By: Relevance
“…A recent mouse study showed that T. cruzi induces a disruption of cholesterol homeostasis which may play an important role in the development of different disorders seen in Chagas disease. 8 In our study, we observed that AI increased as disease severity progressed, reaching its highest values in CCHD III cases.…”
Section: Resultssupporting
confidence: 54%
“…A recent mouse study showed that T. cruzi induces a disruption of cholesterol homeostasis which may play an important role in the development of different disorders seen in Chagas disease. 8 In our study, we observed that AI increased as disease severity progressed, reaching its highest values in CCHD III cases.…”
Section: Resultssupporting
confidence: 54%
“…T. cruzi has high affinity for cholesterol (LDL and HDL) and uses LDL receptors and scavenger receptors to invade various host cells [7, 8, 16, 17]. We measured LDL receptor levels in WAT (d 10pi) and heart (d 20pi) at early acute phase and active acute phase respectively since at these respective time points we observed significant initiation of pathological changes in these tissues (these time points were also chosen to avoid loss of animals due to death from infection) [4, 8].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, considering the evidence that associates T. cruzi with the adipose tissue, ApoA1 and with HDL and LDL modifications, as well as its interaction with LDL receptors [95], the serum lipid profile is an interesting and important metabolome component in the search for possible CD biomarkers. Lipidomics has been defined as "the full characterization of lipid molecular species and of their biological roles with respect to expression of proteins involved in lipid metabolism and function, including gene regulation."…”
Section: Omics-based Applicationsmentioning
confidence: 99%